MENINGKATKAN MUTU PENDIDIK DI KELAS 1 DENGAN METODE KEARIFAN LOKAL MELALUI PERMAINAN CONGKLAK DI SDN CIGEBAR - Ramlan, Ramlan; Elis Halimah, Elis Halimah; Cepi Hidayat, Cepi Hidayat (Wali Pikir: Journal Of Education, 2024)
In the midst of the complexity of global challenges and technological developments, improving the quality of educators at SDN Cigebar is the main focus in responding to the demands of the times. Educators, as key change agents, have a big responsibility in preparing future generations to face increasingly dynamic changes. Therefore, this research aims to explain the concept of improving the quality of educators and its positive impact on the education system. In addition, this research also analyzes various strategies and approaches, including training, professional development, and best practices in education, that can be used to improve the quality of educators. Improving the quality of educators has become a global agenda, in line with increasingly high expectations from society regarding the quality of education provided to the younger generation. The main focus of the research is to find solutions to improve the quality of educators through integrated quality management, involving various stakeholders in education, such as school principals, teachers, administrative staff, parents and the community. Various efforts to improve the quality of education were discussed, starting from teacher training and development, responsive curriculum development, use of educational technology, to active involvement of parents and the community. In an ever-changing global context, improving the quality of education is considered very important to create a competent and competitive society. This research also highlights the key role of teachers in developing the quality of education. Teachers, as the main agents in the educational process, have a vital role in forming the young generation and preparing them to face a future full of challenges. Focusing on teacher professional competence is a priority, because competent teachers can provide a more meaningful and adequate learning experience for students. Furthermore, this research tries to link learning methods based on local wisdom through the traditional game congklak with improving the quality of education in class 1 of SDN Cigebar. By exploring the potential of local wisdom, this research tries to provide concrete and innovative solutions to improve the quality of learning, strengthen student engagement, and create a learning environment that supports children's holistic development. In the process, research identified several problems, such as low quality of learning and lack of student engagement. The local wisdom method using the congklak game is proposed as a solution to stimulate students' intelligence and involvement more actively in the learning process. Thus, this research has important implications in shaping the direction of better education policy and making a positive contribution to improving the quality of education, especially in class 1 of SDN Cigebar. It is hoped that the results of this research will provide valuable insights and recommendations for improvement in efforts to improve the quality of educators in the education system more broadly.